Feasibility of a Pilot Home Phlebotomy Program for Pediatric Hematology/Oncology Patients During the COVID-19 Pandemic. Issue 1 (January 2022) - Sisler, India; Cohen, Debra; Skinner, Lee Ann; Aiken, Crystal; Laver, Joseph
Abstract : Medical care during the Coronavirus 2019 global pandemic required significant shifts in health care delivery systems. Telehealth was widely deployed but was of limited utility for patient populations who rely heavily on laboratory monitoring. This includes pediatric hematology and oncology patients. We report on the feasibility and successful implementation of a home phlebotomy program that has minimized disruption in care for this high-risk patient population. During the initial months of the COVID-19 outbreak, we completed 189 home phlebotomy visits for pediatric hematology and oncology patients. Patient and staff satisfaction with the program were high, and potential exposures to COVID were avoided.